Editorial: Social Media and Identifiers - Campbell, Leith H (Journal of Telecommunications and the Digital Economy, 2024)
This editorial offers some observations about recent moves by the Australian Government to restrict access to social media by young people. It also outlines the other content of this December issue and notes some personnel changes in 2025.